Effect of glutamine on the total antioxidant system of rats subjected to renal ischemia and reperfusion - Gouvêa Junior,Valter Torezan (2011)
PURPOSE: To evaluate the protective effects of glutamine administered before renal ischemia-reperfusion on plasma antioxidant protection, and lung and renal tissue injury. METHODS: 33 rats underwent right nephrectomy. On the eighth postoperative day, animals were randomized into three groups (n=11): glutamine, control and sham. Each group of animals received, by gavage, a particular diet for 7 days. On day 14 following nephrectomy, the animals were subjected to left renal ischemia-reperfusion. After this, blood samples were collected and the animals were killed. At necropsy the kidney and lung were removed for histology. RESULTS: The levels of total antioxidant capacity were higher in the glutamine group and control group compared with the sham group. The levels of glutathione peroxidase in both the sham and glutamine groups were higher when compared with the control group (p<0.05). The level of superoxide dismutase in the sham group was clearly higher than that in the glutamine and control groups. Histological examination showed no differences between the three groups. CONCLUSION: Prior intake of glutamine improves total antioxidant capacity and increases glutathione peroxidase levels in rats subjected to renal ischemia-reperfusion.